Is there any still undisclosed biodiversity in Ciauscolo salami? A new glance into the microbiota of an artisan production as revealed by high-throughput sequencing. (July 2020) - Belleggia, Luca; Milanović, Vesna; Ferrocino, Ilario; Cocolin, Luca; Haouet, M. Naceur; Scuota, Stefania; Maoloni, Antonietta; Garofalo, Cristiana; Cardinali, Federica; Aquilanti, Lucia; Mozzon, Massimo; Foligni, Roberta; et al.
Abstract: Ciauscolo is a fermented sausage with the Protected Geographical Indication (PGI) status. To disclose the microbial ecology of a model Ciauscolo salami manufacture during its natural fermentation, viable counting, amplicon-based sequencing and real-time PCR were applied. The volatilome during fermentation was also characterized. The results allowed previously undetected species to be discovered. The core microbiota was composed by Lactobacillus algidus, Leuconostoc carnosum, Lactobacillus sakei, Debaryomyces hansenii, Glomus hyderabadensis, Tilletiopsis washingtonensis, and Kurtzmaniella zeylanoides . Salmonella spp. and Listeria monocytogenes were absent in all the samples; moreover, multiplex real-time PCR revealed the absence of the target genes bont/A, bont/B, bont/E, bont/F, and 4gyrB (CP ), encoding botulinic toxins. Volatilome, deeply depending on microbiological metabolism, was characterized by spices-derived components. Limonene, sabinene, α- and β-pinene, 3-carene, and α-thujene were the most represented monoterpene hydrocarbons, whereas β- and α-copaene were the most represented sesquiterpene hydrocarbons. Allyl methyl sulphide and diallyl disulphide were the major aliphatic sulphur compounds, together with diallyl sulphide and allyl methyl disulphide. Highlights: The microbiota of Ciauscolo salami was studied through high-throughput sequencing. L. algidus, L. carnosum and L. sakei constituted the core bacterial biota. D. hansenii, G. hyderabadensis, K. zeylanoides prevailed among eumycetes. Volatile profiles were dominated by the spices-derived components. A still undisclosed biodiversity in Ciauscolo salami was evidenced.